Analysis of Labor Figures and Factors Affecting Unemployment in Malang City - Rusdianti, Imanita Septian; Ainun, Siti Nur (PANGRIPTA, 2024)
The phenomenon of this research is an analysis of the dynamics of employment and unemployment in Malang City. The aim of this research is to provide a comprehensive picture of the challenges faced by Malang City in managing the workforce and reducing the unemployment rate. The method in this research uses a qualitative descriptive analysis approach which is used in this research to enable an in-depth understanding of complex phenomena such as employment dynamics. The analysis strategy applied is also relevant and in accordance with the research objective of identifying factors that influence the unemployment rate in the region. These results and discussions present and provide valuable insight into fluctuations in labor force participation rates, open unemployment rates, and unemployment patterns according to education level in Malang City. This finding regarding the mismatch between the skills possessed by graduates and the demands of the job market highlights the importance of synchronizing the educational curriculum with industry needs. In addition, the policy recommendations provided, such as facilitating the transition from education to the world of work and increasing the relevance of the education curriculum to industry needs, are important strategic steps to improve employment conditions and reduce the unemployment rate in Malang City.